Acute flaccid paralysis - Muliai Baalaaji; Muralidharan Jayashree (Wolters Kluwer Medknow Publications, 2015)
Acute flaccid paralysis is an emergency and includes a variety of diagnostic possibilities. Identification of life threatening problems and emergency stabilization should precede further diagnostic evaluation. The common differential diagnoses in the post polio eradication era include Guillain Bane syndrome, acute transverse myelitis and traumatic neuritis. It is essential to rule out reversible causes such as hypokalemia and snake envenomation in the appropriate clinical setting. Stabilization of spine is imperative when trauma is suspected, and early neuroimaging is essential in any child who presents with features of myelopathy to mie out compressive lesions. Careful monitoring of respiratory muscle strength is essential especially in children who progress rapidly and early institution of mechanical ventilation is essential. Management of these children is largely supportive, and includes appropriate ventilator support, provision of early enteral nutrition, physical therapy, strict asepsis, good musing care, bowel and bladder care and psychosocial support. Immunotherapy is useful in certain patients with Guillain Bane syndrome, transverse myelitis and myasthenic crisis. Prolonged ventilation is anticipated in children with severe disease and necessitates tracheostomy to increase patient comfort and facilitate weaning from ventilation. Children who are admitted in intensive care for various disease processes may develop weakness due to critical illness related neuromuscular weakness, no effective treatment exists and management is aimed at identification of risk factors and prevention strategies.